Bilateral deep brain stimulation of the nucleus accumbens for comorbid obsessive compulsive disorder and Tourette's syndrome. (13th September 2012) - Sachdev, Perminder Singh; Cannon, Elisabeth; Coyne, Terry J; Silburn, Peter
Abstract : We present the case of a 32-year-old Caucasian woman with severe treatment-refractory obsessive compulsive disorder (OCD) and Tourette's syndrome. Both conditions were present prior to age 5 and impacted significantly on the patient's functioning. Multiple trials of evidence-based pharmacological and behavioural therapies had not achieved remission of symptoms. Bilateral deep brain stimulation of the nucleus accumbens was undertaken to treat both illnesses but with a particular focus on OCD, as the patient identified this as the more debilitating of the two disorders. Following surgery there was an immediate improvement in OCD and tic severity. At follow-up 8 months later, there was a 90% improvement in OCD symptoms and a 57% improvement in tic severity. No intraoperative or postoperative complications or adverse events occurred and there were no undesired effects of stimulation.